“Estrategias lúdicas para la convivencia escolar” - Mónica Gissela, Cuji Cunalata (2024)
Play strategies are fundamental activities that influence the academic, social and emotional development of students. These activities act as determinants in the formation of interpersonal relationships and conflict resolution to improve school coexistence. The research problem arises because there are relationship problems between students and teachers due to the scarce use of play strategies, which hinders good school coexistence. The objective of this research project was to determine play strategies aimed at the prevention of conflicts that affect middle school students in order to strengthen school coexistence in the ‘Arcelia German’ elementary school, located in the Mulalillo parish, Salcedo canton, Cotopaxi province, in the current school year 2023-2024. The study methodology was based on the positivist paradigm, with a quantitative approach, using descriptive research, as well as the deductive method. The main technique used to collect the information was the survey and the questionnaire was used as an instrument. The population consisted of students, parents and teachers. These instruments made it possible to obtain detailed information about the play strategies and the impact on school coexistence. As a result, a statistical analysis of the application of play strategies and school coexistence was obtained. This study allowed us to identify effective play strategies to avoid conflicts that affect the social and emotional well-being of students, as well as the elements that contribute to creating a collaborative and safe school environment.